Antimicrobial activity: potential of Spondias purpurea (Anacardiaceae) against bacterial and fungal species - de Oliveira, Thais Emboaba [UNESP]; Greatti, Vanessa Raquel [UNESP]; Sorrechia, Rodrigo [UNESP]; Pietro, Rosemeire C.L.R. [UNESP] (Microbiology Society, 2022)
Introduction. Plants have been used as medicines for centuries to treat human diseases. Studies with plants are extremely important for the development of future drugs that can benefit the human population. Hypothesis/Gap Statement. With the emergence of pathogens resistant to antimicrobial agents, there is an urgent need to direct research towards the discovery of new antimicrobials. Aim. In this study, Spondias purpurea L. (Anacardiaceae) was evaluated for its antimicrobial activity, antioxidant activity and cytotoxicity. Methodology. Antimicrobial activity was evaluated by the MIC using the 96-well plate microdilution technique of ethanolic, hexanic and dicloromethanic extracts of dried S. purpurea leaves against bacteria, yeast and filamentous fungi. The antioxidant activity of extracts was evaluated by the 2, 2-diphenyl-1-picrylhydrazine (DPPH) method. To evaluate the safety of extracts, a cytotoxicity study against HaCat, J774 and HepG2 cells was performed. Results. The extracts had no activity against the bacteria at the maximum concentration of 5.0 mg ml−1, but showed fungistatic action against Candida species and dermatophytes. The ethanolic extract showed 88% antioxidant activity and showed no significant cytotoxicity against the previously mentioned cells. Conclusion. This study showed that the 100% ethanolic (EtOH) extract was favourable for antifungal and antioxidant activities and did not present significant cytotoxicity against the three studied cell lines, indicating that S. purpurea leaves are promising for the development of new antimicrobials.
Keywords: Anacardiaceae; antimicrobial activity; antioxidant activity; cytotoxicity; seriguela; Spondias purpurea